Outcome of continued infliximab therapy in Crohn's disease patients with response but without remission after one year of infliximab – a retrospective cohort study. (3rd August 2018) - Buhl, Sine; Kristina Borghede, Märta; Brynskov, Jørn; Steenholdt, Casper; Rasmussen, Maria; Andrew Ainsworth, Mark
Abstract: Background: Optimal management of Crohn's disease patients having responded to infliximab but without achieving remission is not well defined. The present study examined if these patients benefit from continued long-term infliximab maintenance therapy. Method: Retrospective cohort study including all patients treated with infliximab for 1 year until the end of 2017 who have had a response but not reached remission on infliximab. Clinical outcomes were defined by the physicians' global evaluation, supported by clinical indices and objective markers of disease activity. Results: In total, 376 Crohn's disease patients received infliximab. Among these, 76 (20%) were classified as having response but non-remission (RNR) after 1 year of therapy. A great majority ( n  = 54; 71%) experienced no additional therapeutic benefit after a further year of infliximab maintenance therapy, thus still having RNR. Nineteen patients (25%) obtained remission during continued infliximab, whereas only 4% ( n  = 3) experienced treatment failure. Although infliximab therapy beyond 2 years (follow-up median 35 months, IQR: 23–55) was accompanied by a higher proportion attaining remission (40%), nearly half (46%) still failed to improve. Among patients who had discontinued infliximab while having RNR ( n  = 21), half ( n  = 11) experienced disease flare within five months (median 22 weeks, IQR: 12–31). Conclusion: Most patients (71%) had no additional therapeutic benefit after an additional year of infliximab therapy, and after a median maintenance infliximab treatment period of 3 years, half still failed to improve further. Considering the importance of achieving complete remission, these patients appear to have an unmet medical need.